1983
DOI: 10.1073/pnas.80.3.750
|View full text |Cite
|
Sign up to set email alerts
|

Adiabatic compressibility of globular proteins.

Abstract: The adiabatic compressibility of several globular proteins has been measured by using an ultrasonic technique in the frequency range 0.5 to 10 MHz. The contributions to the measured-compressibility from the protein matrix .and from surface processes involving ionization of side chains and solvation effects are discussed; The internal -protein compressibility is very. low, indicating the existence of "dynamic domains" which are tentatively assigned to secondary structure elements.During the past few years, cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
95
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(104 citation statements)
references
References 38 publications
7
95
2
Order By: Relevance
“…It is possible that the effects of volume changes on the energy of the native state could be offset by comparable effects on the denatured state. A direct analysis of this phenomenon appears problematic, however, because both ␣ and ␤ for the protein-solvent system change on denaturation in a protein-dependent fashion (Brandts et al 1970;Hawley 1971;Zipp and Kauzmann 1973;Gavish et al 1983;Prehoda et al 1998;Panick et al 1999) that has been difficult to generalize in terms of the relative consequences on (dE/ dV) T .…”
Section: Temperature Dependence Of Protein Structurementioning
confidence: 99%
“…It is possible that the effects of volume changes on the energy of the native state could be offset by comparable effects on the denatured state. A direct analysis of this phenomenon appears problematic, however, because both ␣ and ␤ for the protein-solvent system change on denaturation in a protein-dependent fashion (Brandts et al 1970;Hawley 1971;Zipp and Kauzmann 1973;Gavish et al 1983;Prehoda et al 1998;Panick et al 1999) that has been difficult to generalize in terms of the relative consequences on (dE/ dV) T .…”
Section: Temperature Dependence Of Protein Structurementioning
confidence: 99%
“…They concluded that pressure alters both the relative substate populations and the functional properties of the individual substates and, thus, can produce large changes in the static and dynamic properties of a protein ensemble. The effect of pressure on protein structure also has been described in terms 121 of cavity reduction inside the protein matrix as well as changes in the hydration of mainly peripheral regions of the polypeptide chain (Heremans, 1982;Gavish et al, 1983;Nolting & Sligar, 1993;Silva & Weber, 1993;Cioni & Strambini, 1994;Jonas & Jonas, 1994).…”
mentioning
confidence: 99%
“…For example, the number of hydrophobic amino acids and the type of secondary structures are believed to contribute to the compressible properties of a protein (Gavish et al, 1983;Gekko and Hasegawa, 1986). However, the primary and secondary structures of proteins are poorly correlated with the compressible properties of different proteins (Gavish et al, 1983;Gekko and Yamagami, 1991;Dadarlat and Post, 2001). For instance, a high homology between hen egg lysozyme and bovine milk α-lactalbumin is found in the primary (45% homology) and the secondary (29-33%…”
Section: Compressible Properties and Protein Structurementioning
confidence: 99%
“…When examining the structure of a protein molecule, a number of different structural levels are apparent (Gavish et al, 1983;Gekko et al, 1996). It would be expected that each of the various structural levels would affect the compressibility of the protein molecule.…”
Section: Compressible Properties and Protein Structurementioning
confidence: 99%
See 1 more Smart Citation